Chemical composition and in vitro digestibility of some range plants - Musa Ahmed Musa Tibin; Badreldeen Mohammed Musa Ibrahim; Suleiman Eshag Mohamed Abdalla; Yahia Ibrahim Mohammed Abutaba; Jumaa Barram Jadalla; Mohammed Alhadi Ebrahiem (Open Journal of Plant Science - Peertechz Publications, 2021)
This study was carried out to determine chemical composition and in vitro dry matter and organic matter digestibility of range plant species of the area. Samples were collected from range lands at full maturity stage, dried under shade and subjected to chemical analysis and dry matter and organic matter in vitro digestibility for Vigna sunhum, Andropogan gayanus, Pennisetum Pedicelatum, Shoenfeldia gracilis and Stylothanis flavicans were determined. The data was analyzed via analysis of variance and differences among means were determined using Least Significant Difference (LSD) test. The results showed that the legumes (Vigna sunhum and Stylothanis flavicans) were significantly higher (P≤0.01) in their crude protein content and the percentage of crude protein respectively was 13.4% and 10.00% while the grasses were significant (P≤0.05) higher in Crude Fibre (CF), ash, Acid Detergent Fibers (ADF) and Neutral Detergent Fibers (NDF). Crude fiber % values were 41.78, 43.37 and 46.07% for Pennisetum Pedicelatum, Andropogan gayanus and Shoenofeldia gracilis, respectively. The acid detergent values were 53.85, 47.74 and 53.39 for the three weeds. (P≤0.05), while the ratio of neutral detergent was significantly higher (P≤.05) in grasses than in the two legume species; 87.22, 82.35 and 88.99% for the three grasses respectively. Similarly higher in vitro dry matter and organic digestibility coefficients were obtained from legume species than grasses. The study concluded that, the studied grasses were higher in fiber content and lower in their protein content but, legumes grasses (Vigna sunhum, Pennisetum Pedicelatum and Stylothanis flavicans) had high nutritive value and in vitro digestibility which may provide ruminants with the needed protein and energy.